Effectiveness of an Interactive, Highly Tailored "Video Doctor" Intervention to Suppress Viral Load and Retain Patients With HIV in Clinical Care: A Randomized Clinical Trial. (1st September 2022) - Lewis, Megan A.; Harshbarger, Camilla; Bann, Carla; Marconi, Vincent C.; Somboonwit, Charurut; Piazza, Michelle Dalla; Swaminathan, Shobha; Burrus, Olivia; Galindo, Carla; Borkowf, Craig B.; Marks, Gary; Karns, Shawn; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: To determine whether Positive Health Check, a highly tailored video doctor intervention, can improve viral suppression and retention in care. Setting: Four clinics that deliver HIV primary care. Methods: A hybrid type 1 effectiveness-implementation randomized trial design was used to test study hypotheses. Participants (N = 799) who were not virally suppressed, were new to care, or had fallen out of care were randomly assigned to receive Positive Health Check or the standard of care alone. The primary endpoint was viral load suppression, and the secondary endpoint was retention in care, both assessed at 12 months, using an intention-to-treat approach. A priori subgroup analyses based on sex assigned at birth and race were examined as well. Results: There were no statistically significant differences between Positive Health Check (N = 397) and standard of care (N = 402) for either endpoint. However, statistically significant group differences were identified from a priori subgroup analyses. Male participants receiving Positive Health Check were more likely to achieve suppression at 12 months than male participants receiving standard of care adjusted risk ratio [aRR] [95% confidence interval (CI)] = 1.14 (1.00 to 1.29), P = 0.046}. For retention in care, there was a statistically significant lower risk for a 6-month visit gap in the Positive Health Check arm for the youngest participants, 18–29 years old [aRR (95% CI) = 0.55 (0.33 to 0.92), P = 0.024] and the oldest participants, 60–81 years old [aRR (95% CI) = 0.49 (0.30 to 0.81), P = 0.006]. Conclusions: Positive Health Check may help male participants with HIV achieve viral suppression, and younger and older patients consistently attend HIV care. Registry Name: Positive Health Check Evaluation Trial. Trial ID: 1U18PS004967-01. URL: https://clinicaltrials.gov/ct2/show/NCT03292913 .